Positive Pollutions and Cultural Toxins : Waste and Contamination in Contemporary U.S. Ethnic Literatures. - Gamber, John Blair (Postwestern horizons., 2012)
In this innovative study, Positive Pollutions and Cultural Toxins, John Blair Gamber examines urbanity and the results of urban living-traffic, garbage, sewage, waste, and pollution-arguing for a new recognition of all forms of human detritus as part of the natural world and thus for a broadening of our understanding of environmental literature. While much of the discourse surrounding the United States' idealistic and nostalgic views of itself privileges "clean" living (primarily in rural, small-town, and suburban settings), representations of rurality and urbanity by Chicanas/Chicanos, Afric.